How servant leadership affects job satisfaction and organizational commitment in the post COVID-19 era - Bevanda Nevena; Bevanda Vuk; Pavlović Goran (Anali Ekonomskog fakulteta u Subotici, 2025)
This study aims to investigate how servant leadership influences job satisfaction and organizational commitment in the post-COVID-19 era. Its objective is to understand how servant leadership, with its focus on empathy and employee well-being, has influenced these key organizational outcomes following the challenges brought by the pandemic. Primary data were collected using a survey method, and descriptive statistics, correlation, and simple regression were employed to analyze the data. The data collection took place in September 2024, with a sample of 101 respondents. The main requirement for the sample was that respondents work in an organization located in Serbia. The results show that servant leadership significantly influences both job satisfaction and organizational commitment. These findings underscore the importance of satisfied and committed employees in driving organizational efficiency, effectiveness, and performance. This paper might be of interest to leaders, HR professionals, researchers in leadership and management, and policymakers. It offers actionable recommendations for integrating servant leadership principles into HRM strategies to strengthen team cohesion, enhance employee engagement, and improve organizational outcomes. Furthermore, the findings serve as a valuable resource for shaping future HRM decisions and strategies.